'My Mom Got Influenced by Yours': The persuasiveness of mom influencers in relation to mothers' food assessments and decisions. (1st November 2022) - Beuckels, Emma; De Jans, Steffi
Abstract: Childhood obesity is a worldwide health problem with a range of short- and long-term health and social consequences; however, the World Health Organization (WHO) argues that this epidemic is preventable and reversible. The biggest dietary gatekeepers of children are their parents and more specifically mothers, whose attitudes and consumption choices are nowadays often affected by the opinions of influencers on social network sites (SNSs). Using two experimental studies, the current paper investigates how mothers' food assessments and decisions for their children are affected by sponsored posts on social media. The first study adopted a two-level between-subjects experiment ( N  = 81), which showed that mothers like sponsored Instagram posts better when they are posted by a mom influencer (i.e. a mother who accumulated a large following on social media and often engages in sponsored partnerships with brands) compared to a brand. This consequently positively affected source credibility, post engagement, purchase intention and the child appropriateness of the food. In the second experiment, a two-by-two between-subjects design ( N  = 169) showed that while a typical mom influencer is perceived as less effective in promoting food compared to an expert (i.e. a pediatric nutritionist) mom influencer due to lower credibility, a typical mom influencer is more efficient in promoting unhealthy foods through higher influencer-brand congruence.